(untitled) (Journal of Economic Research & Business Administration, 2021)
The article considers the problems of aggravation of the demographic situation in rural areas, caused on the one hand by the mechanical outflow of the able-bodied population and, on the other hand, by natural decline in fertility and relatively short life expectancy. Meanwhile, Kazakhstan has adopted a state program for the development of the agro-industrial complex for 2017 – 2021 years. Agriculture, as the core of the agro-industrial complex, has important tasks to ensure the physical and economic accessibility of food to the general population, increase the efficiency of the use of natural resources, develop agricultural science and transfer of technologies, introduce digital technologies and improve the quality of life of the rural population. Declining demographic potential in rural areas in the future may adversely affect the rate of reproduction of the population as a whole, the state and even the degradation of rural areas. The purpose of the article is not only a statistical analysis of the rate of reproduction of the rural population, a study of the demographic situation in rural areas, but also the justification of a set of measures to prevent demographic threats, solve the problem of food security, and sustainable social and economic development of rural areas. To achieve the goal, dialectical, historical, statistical-economic, comparative methods were used. Authors allocate the labor capacity of rural territories as a major factor of ensuring competitiveness of the rural area, the region and the country in general. Key words: rural population, demography, migration, outflow, labor resources.